2011
DOI: 10.4061/2011/274564
|View full text |Cite
|
Sign up to set email alerts
|

The Haematopoietic Stem Cell Niche: New Insights into the Mechanisms Regulating Haematopoietic Stem Cell Behaviour

Abstract: The concept of the haematopoietic stem cell (HSC) niche was formulated by Schofield in the 1970s, as a region within the bone marrow containing functional cell types that can maintain HSC potency throughout life. Since then, ongoing research has identified numerous cell types and a plethora of signals that not only maintain HSCs, but also dictate their behaviour with respect to homeostatic requirements and exogenous stresses. It has been proposed that there are endosteal and vascular niches within the bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 115 publications
0
43
0
Order By: Relevance
“…HSCs occur in the vicinity of, but not necessarily in direct contact with, osteoblastic bone-lining cells that constitute the endosteal niche regions. However, the sinusoidal endothelium also interacts with HSCs, and form the vascular niche (6 suggests that their effects may be more complicated due to functional crosstalk between cells within the two regions (8,9). Furthermore, the vascular niche has been suggested to regulate HSCs in a distinct mechanism or potentially harbor HSCs with various self-renewable properties (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…HSCs occur in the vicinity of, but not necessarily in direct contact with, osteoblastic bone-lining cells that constitute the endosteal niche regions. However, the sinusoidal endothelium also interacts with HSCs, and form the vascular niche (6 suggests that their effects may be more complicated due to functional crosstalk between cells within the two regions (8,9). Furthermore, the vascular niche has been suggested to regulate HSCs in a distinct mechanism or potentially harbor HSCs with various self-renewable properties (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Notch receptors on HSCs has been shown to inhibit differentiation and enhance their self renewal capacity in vitro (Butler et al, 2011). Notch signalling is important in vivo for controlling HSC self renewal and differentiation during hematopoietic stress conditions (Lilly et al, 2011).…”
Section: Osteoblastic Cellsmentioning
confidence: 99%
“…These cytokines are thought to be important as THPO and Ang-1 knockout mice have decreased numbers or defects in bone marrow HSCs. The interaction of Ang-1 with its Tie2 receptor activates β1-integrin and Ncadherin, enhances quiescence, and maintains the long term repopulating ability of HSCs; it also protects against apoptosis by activating the PI3K pathway (Lilly et al, 2011) • Osteopontin, a matrix glycoprotein expressed by the osteoblasts supports the adhesion of HSC to the osteoblastic niche and negatively regulates HSC proliferation, contributing to the maintenance of a quiescent state (Guerrouahen et al, 2011). …”
Section: Osteoblastic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of cellular compartments of the HSC niche has recently been the subject of many studies (Bianco, 2011;Morrison et al, 2014). In bone marrow (BM), there is broad discussion of the possible presence of two niches able to maintain and regulate HSCs, which are the endosteal and vascular niches (Lilly et al, 2011). Previous reports suggested that N-cadherin + osteoblasts could be proposed to promote HSC quiescence through direct contact and secretion of some cytokines and extracellular matrix proteins (Bromberg et al, 2012;Greenbaum et al, 2012).…”
Section: Introductionmentioning
confidence: 99%